WORLDVIEW-FORMING INFLUENCES OF CHILDREN’S LITERATURE IN THE CONDITIONS OF THE FULL-SCALE RUSSIAN INVASION OF UKRAINE - SHYNKARYK, Iuliana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Annotation. The study is devoted to book publishing for children in the conditions of a full-scale Russian invasion of Ukraine. The work analyzes the worldview-forming influences of literature about the war for younger readers. It was established that the transformation of the educational landscape cannot be properly implemented without strong children's books. It was determined that publishers should be offered such a product that can fit into the national information and communication space. It has been proven that for the sake of effective transformations, the formation of a worldview core in childhood, military-patriotic education and the book should act as a single coordinated mechanism - this is the only way to launch worldview-educational changes, the focus of which will be a children's book. The author traces the peculiarities of publishing books on the topic of war for children in the modern stage. Problems related to communication with children about the war were identified. Attention is paid to key books about the war for children, their textual and illustrative material. Among the outlined issues is the way this topic is presented by the authors of children's works, the realism of the depicted events, the focus on memories, and the appeal to fantasy plots. Illustrations are also an important component of children's book publishing, in particular books with illustrations drawn by children, which, in turn, confirms their maturity and the need to raise difficult topics about the state of the modern world. It has been proven that children's literature about war, especially in wartime, is an important factor in information security. A Ukrainian studies analysis of children's publications in Ukraine on the topic of war was carried out. A comparison of illustrative material in children's books is made, as a kind of multimodal form of communication, where text and images interact with each other, which is a means of forming the semantic meaning of the book. Attention is focused on the importance of Ukrainian-language content for children's and adolescent literature.